The Knowledge Level among Third Trimester Pregnant Women on Premature Rupture of Membranes At Immanuela Clinic Batam in 2021 - Ester Laura; Aprilita Br Sitepu (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2021)
Maternal death according to WHO occurs during pregnancy, childbirth, postpartum with causes that are directly or indirectly related to pregnancy. The causes of maternal death include infection 9.6% of live births. Premature rupture of membranes is one element that causes infection that can result in maternal and infant morbidity and mortality. So that lack of knowledge can indirectly form attitudes and behavior in making decisions in the event of premature rupture of membranesThis type of research uses a descriptive quantitative method with a sample of pregnant women. The number of samples is 24 respondents with the sampling technique used is Accidental Sampling, questionnaire instrument, univariate analysis with percentage results.The results obtained from 24 respondents, the level of knowledge of pregnant women about premature rupture of membranes at Immanuela clinic Batam has the most knowledge (45.8%) totaling 11 respondents. Most of the pregnant women aged 20-35 years (87.5%) amounted to 21 respondents with a high school education level (66.66%) totaling 16 respondents, and pregnant women with multigravida (62.5%) totaling 15 respondents.The level of knowledge of pregnant women about premature rupture of membranes at Immanuela Clinic Batam is categorized as "Enough" with most pregnant women aged 20-35 years with a high school education level and the majority of mothers being multigravida.